Sorting the trash: Micronucleophagy gets selective - Verlhac, Pauline (J Cell Biol, 2018)
During micronucleophagy, the nucleolus is targeted by autophagic degradation, but although nucleolar proteins are recycled, ribosomal DNA is spared. Mostofa et al. (2018. J. Cell Biol. https://doi.org/10.1083/jcb.201706164) reveal that the separation of these two nucleolar components is mediated by the CLIP and cohibin complexes and is vital for cell survival during starvation.